Произносительные особенности алеманнских диалектов - Щелкова, Е.Е. (Культура народов Причерноморья, 2004)
Целью данной статьи является выделение произносительных особенностей алеманнских диалектов и их сопоставление с фонетической системой литературного языка. Метою даної статті є виділення вимовних особливостей алеманськіх діалектів і їх зіставлення з фонетичною системою літературної мови The scientific study of dialects is an essential part of linguistics and deals with the geographical and territorial variations of a given language. As to the German language, dialect is seen in opposition to what is called standard German or High German. In comparing dialect with standard German one discovers a complete list of typical features and characteristics of a dialect. Dialect came into existence much earlier than the standard type of the language and, therefore, is widely spread in the German territories.